Clinical Predictors of Cardiac Arrest among COVID-19 Patients with Heart Failure - Marwaha, Bharat; Mahata, Indrajeet; Kumar, Navneet; Singh, Goldendeep; Amritphale, Amod (Cardiology and Cardiovascular Medicine, 2024)
The COVID-19 pandemic has impacted the healthcare system across the globe, leading to more than 6.9 million deaths in the past four years. Cardiac Arrest is a terminal event with associated significantly high morbidity and mortality across age groups. Multiple clinical parameters, organ dysfunction, and chronic co- morbid conditions impact mortality in COVID-19 patients with heart failure. In this retrospective, administrative dataset-based study on 148899 patients admitted to the hospital with COVID-19 and heart failure diagnosis, we reported 6703 cardiac arrests and 5783 mortality. We have used ICD 10 codes to identify the diagnosis. The primary objective of the study is to find the predictors of Cardiac Arrest among patients admitted to hospitals with COVID-19 and heart failure. Secondary objective is to calculate the percentage of cardiac Arrest and mortality across the various age groups and the correlation of hours on the mechanical ventilator and mortality. Study results have shown that the use of a mechanical ventilator has the strongest co- correlation with cardiac Arrest with an odd ratio of 14.4, followed by septic shock with an odd ratio of 5.6, tension pneumothorax with an odd ratio of 4.9 preceding the acute renal failure with an odd ratio of 2.4 and sepsis 2.3. Complete heart block had an odd ratio of 1.9, followed by ESRD with a ratio of 1.6, acute pulmonary embolism with an odd ratio of 1.5, and Type 2 MI with an odd ratio of 1.49. Chronic co-morbid condition of DM had an odd ratio of 1.3, followed by Atrial fibrillation with an odd ratio of 1.1. These results and findings emphasized that multi-organ failure has a huge impact on cardiac Arrest among COVID-19 patients with heart failure.